Adaptive hybrid fuzzy-proportional plus crisp-integral current control algorithm for shunt active power filter operation - Abdul Rahman, Nor Farahaida; Mohd Radzi, Mohd Amran; Che Soh, Azura; Mariun, Norman; Abd Rahim, Nasrudin (MDPI, 2016)
An adaptive hybrid fuzzy-proportional plus crisp-integral current control algorithm (CCA) for regulating supply current and enhancing the operation of a shunt active power filter (SAPF) is presented. It introduces a unique integration of fuzzy-proportional (Fuzzy-P) and crisp-integral (Crisp-I) current controllers. The Fuzzy-P current controller is developed to perform gain tuning procedure and proportional control action. This controller inherits the simplest configuration; it is constructed using a single-input single-output fuzzy rule configuration. Thus, an execution of few fuzzy rules is sufficient for the controller’s operation. Furthermore, the fuzzy rule is developed using the relationship of currents only. Hence, it simplifies the controller development. Meanwhile, the Crisp-I current controller is developed to perform integral control action using a controllable gain value; to improve the steady-state control mechanism. The gain value is modified and controlled using the Fuzzy-P current controller’s output variable. Therefore, the gain value will continuously be adjusted at every sample period (or throughout the SAPF operation). The effectiveness of the proposed CCA in regulating supply current is validated in both simulation and experimental work. All results have proven that the SAPF using the proposed CCA is capable to regulate supply current during steady-state and dynamic-state operations. At the same time, the SAPF is able to enhance its operation in compensating harmonic currents and reactive power. Furthermore, the implementation of the proposed CCA has resulted more stable dc-link voltage waveform.